The induced membrane technique for the management of long bone defects: a systematic review of patient outcomes and predictive variables. (1st December 2020) - Fung, Benjamin; Hoit, Graeme; Schemitsch, Emil; Godbout, Charles; Nauth, Aaron
Abstract : Aims: The purpose of this study was to: review the efficacy of the induced membrane technique (IMT), also known as the Masquelet technique; and investigate the relationship between patient factors and technique variations on the outcomes of the IMT. Methods: A systematic search was performed in CINAHL, The Cochrane Library, Embase, Ovid MEDLINE, and PubMed. We included articles from 1 January 1980 to 30 September 2019. Studies with a minimum sample size of five cases, where the IMT was performed primarily in adult patients (≥ 18 years old), in a long bone were included. Multivariate regression models were performed on patient-level data to determine variables associated with nonunion, postoperative infection, and the need for additional procedures. Results: A total of 48 studies were included, with 1, 386 cases treated with the IMT. Patients had a mean age of 40.7 years (4 to 88), and the mean defect size was 5.9 cm (0.5 to 26). In total, 82.3% of cases achieved union after the index second stage procedure. The mean time to union was 6.6 months (1.4 to 58.7) after the second stage. Our multivariate analysis of 450 individual patients showed that the odds of developing a nonunion were significantly increased in those with preoperative infection. Patients with tibial defects, and those with larger defects, were at significantly higher odds of developing a postoperative infection. Our analysis also demonstrated a trend towards the inclusion of antibiotics in the cement spacer having a protective effect against the need for additional procedures. Conclusion: The IMT is an effective management strategy for complex segmental bone defects. Standardized reporting of individual patient data or larger prospective trials is required to determine the optimal implementation of this technique. This is the most comprehensive review of the IMT, and the first to compile individual patient data and use regression models to determine predictors of outcomes. Cite this article: Bone Joint J 2020;102-B(12):1723–1734.